CANNUSE, a database of traditional Cannabis uses—an opportunity for new research. (1st May 2021) - Balant, Manica; Gras, Airy; Gálvez, Francisco; Garnatje, Teresa; Vallès, Joan; Vitales, Daniel
Abstract: Cannabis is one of the most versatile genera in terms of plant uses and has been exploited by humans for millennia due to its medicinal properties, strong fibres, nutritious seeds and psychoactive resin. Nowadays, Cannabi s is the centre of many scientific studies, which mainly focus on its chemical composition and medicinal properties. Unfortunately, while new applications of this plant are continuously being developed, some of its traditional uses are becoming rare and even disappearing altogether. Information on traditional uses of Cannabis is vast, but it is scattered across many publication sources in different formats, so synthesis and standardization of these data are increasingly important. The CANNUSE database provides an organized information source for scientists and general public interested in different aspects of Cannabis use. It contains over 2300 entries from 649 publications related to medicinal, alimentary, fibre and other uses from different geographical areas and cultures around the world. We believe this database will serve as a starting point for new research and development strategies based on the traditional knowledge. Database URL: http://cannusedb.csic.es